Does neuromuscular electrical stimulation therapy increase voluntary muscle strength after spinal cord injury? A systematic review - De Freitas G.R.* (2018)
© 2017 Thomas Land Publishers, Inc.Background: Physical therapists frequently use neuromuscular electrical stimulation (NMES) therapy in an effort to increase the voluntary strength of partially paralyzed muscles in people with spinal cord injury (SCI), but it is not clear whether this treatment is effective. Objective: To determine the effectiveness of NMES for increasing voluntary strength in the partially paralyzed muscles of people with SCI. Methods: A systematic review of scientific literature was conducted in MEDLINE, CINAHL, PEDro, ScienceDirect, and Embase. Inclusion criteria were randomized controlled trials and controlled trials that compared NMES aimed at increasing strength in partially paralyzed muscles versus placebo/nothing or versus a nonstrengthening intervention or versus any other type of strengthening intervention in adults with SCI. Results: Five studies were included. Two studies found an increase in strength measured by peak force and manual muscle force test after an NMES protocol. One study found a between-group difference in favor of the NMES associated with progressive resistance training, and the other study showed an increase in the number of muscles improved by at least 1 degree of strength after NMES in combination with a cycle ergometer. The other 3 studies made several comparisons and found no differences between groups that received NMES and the controls. Conclusions: There is some suggestion that NMES increases voluntary strength in partially paralyzed muscle following SCI. However, there is no strong evidence to affirm the superiority of NMES over other treatment strategies used to gain strength in partially paralyzed muscles after SCI. These findings need replicating in large high-quality randomized controlled trials.